An economic analysis of online streaming. How the music industry can generate revenues from cloud computing - Tim Paul Thomes (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
This paper investigates the upcoming business model of online streaming services allowing music consumers either to subscribe to a service which provides free-of-charge access to streaming music and which is funded by advertising, or to pay a monthly flat fee in order to get ad-free access to the content of the service accompanied with additional benefits. By imposing a two-sided market model on the one hand combined with a direct transaction between the streaming service and its flat-rate subscribers on the other hand, the investigation shows that it can be highly profitable to launch a business which is free-of-charge for subscribers if advertising imposes a weak nuisance to music consumers. If this is the case, and by imposing an endogenously determined level of advertising which is provided by homogeneous advertisers, we find that a monopolistic streaming service increases the price for its flat-rate subscribers in order to stimulate free-of-charge demand and to capture higher revenues from advertisers. An extension of the model by illegal file-sharing shows that an increase in copyright enforcement shifts rents from music consumers to the monopolist.
urn:nbn:de:bsz:180-madoc-31908; More recent version: http://hdl.handle.net/10419/48872
Keywords: D42; L12; L82; 330; Advertising media; Music industry; Online streaming; Piracy